A nanosuspension of ellagic acid with high solubility and antioxidant activity and its application in oral, topical preparations and cosmetics

The preparation of ellagic acid nanosuspensions through ultrasonic processes solved the problem of low solubility of ellagic acid, significantly improved its antioxidant activity and bioavailability, enhanced the efficacy, and was suitable for oral and topical preparations.

CN115737553BActive Publication Date: 2025-01-03NANJING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211465349.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-02
Filing Date
2022-11-22
Publication Date
2025-01-03
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The extremely low solubility of ellagic acid limits its use in oral and topical formulations, resulting in low antioxidant activity and bioavailability.

Method used

Ultrasonic technology is used to prepare ellagic acid nanosuspensions. By using pure water or a mixed solution of organic solvent and water, ellagic acid nanoparticles with a diameter of 100-1000 nm are formed to improve their solubility and antioxidant activity.

Benefits of technology

It significantly improves the solubility, antioxidant activity and transdermal properties of ellagic acid, increases its oral bioavailability, solves the problem of low solubility, and enhances local and systemic efficacy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115737553B_ABST
    Figure CN115737553B_ABST
Patent Text Reader

Abstract

Ellagic acid is a recognized whitening agent, antioxidant and nutrient, but its solubility is extremely low, which greatly limits its application. The present invention provides an ellagic acid nanosuspension for this problem, comprising ellagic acid nanoparticles with a particle size of 100-1000 nm, which are composed of ellagic acid and a preparation solvent, and the preparation solvent is preferably selected from water, ethanol, propylene glycol, butylene glycol, pentanediol or a mixed solvent thereof; a supersaturated ellagic acid solution is prepared by an ultrasonic process as a preferred embodiment, and the ellagic acid feed amount during preparation is ≥20mg / mL, and the ultrasonic temperature is ≥35°C as a preferred embodiment. The present invention does not need to add auxiliary materials, does not need a complex preparation process, can solve the problems of ellagic acid solubility (equilibrium solubility increases by more than 100 times), oral bioavailability (increased to 4.69 times) and in vitro transdermal absorption (significantly increasing intradermal content and transdermal amount), and simultaneously shows antioxidant activity significantly better than free ellagic acid and positive drug VC. Comprehensively display the development prospects of ellagic acid nanosuspension in the fields of oral, topical preparations and cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of food raw materials, external preparation raw materials and cosmetic raw materials, and specifically relates to an ellagic acid nanosuspension with high solubility and antioxidant activity, which can simultaneously improve the antioxidant activity, solubility, transdermal performance and oral bioavailability. The present invention also relates to the application of the ellagic acid nanosuspension in oral preparations, external preparations and cosmetics. Technical Background

[0002] Ellagic acid (EA), also known as retrogallic acid, is a plant polyphenol with CAS number 476-66-4 and molecular formula C 14 H6O8, molecular weight 302.19Da, melting point>360℃; characteristic wavelengths of ultraviolet absorption are 254nm and 366nm, insoluble in ethers, slightly soluble in water, alcohol, dimethyl sulfoxide, soluble in pyridine and alkaline solutions. It is widely found in various fruits, nuts and other plants, such as grapes, pomegranates, apples, cherries, raspberries, strawberries, blueberries, tara, walnuts, and Euryale ferox, and has a wide range of effects, such as anti-inflammatory, antibacterial, antiviral, especially anti-oxidation, anti-aging, whitening, and astringent. Ellagic acid has been included in the International Standard Catalog of Cosmetic Ingredients (INCI) internationally, and China has also included it in the International Standard Chinese Name Catalog of Cosmetic Ingredients (2015 edition) issued by the State Food and Drug Administration. Ellagic acid has been applied to many types of cosmetics such as whitening and anti-aging due to its high safety, mild effect on the skin and significant efficacy. Functional cosmetics made with ellagic acid as raw material have great research and development value and market prospects.

[0003] Studies have shown that ellagic acid can prevent UVA-induced DNA damage and help treat UVA-induced skin damage. 2- The results showed that ellagic acid has strong anti-aging ability, and it was determined that ellagic acid can be used as a natural free radical scavenger and elastase inhibitor in anti-aging cosmetics, and can also be added as a nutrient to oral preparations such as health foods. At the same time, ellagic acid can inhibit the activity of tyrosinase in melanocytes and block melanogenesis in vitro, which is similar to the whitening effect of L-ascorbic acid on guinea pig skin. Clinically, topical ellagic acid has a whitening effect comparable to that of the whitening agent arbutin, and it is determined that ellagic acid can be used as a whitening agent in whitening cosmetics. However, the solubility of ellagic acid in water is extremely low (<10μg / mL), resulting in extremely low oral bioavailability. These defects greatly limit its application and development, so even with its strong antioxidant ability and whitening effect, it is not widely used in topical preparations and oral preparations.

[0004] Ellagic acid belongs to Class IV of the Biopharmaceutical Classification System (BCS), i.e., low solubility and low permeability drugs. High lattice force (melting point 360°C) is the root cause of the poor solubility of ellagic acid. Some chemical or physical modification methods have been studied for the solubility modification of ellagic acid. Chemical modification includes the development of prodrugs, the formation of salts, and the design of cocrystals. However, changing one property may have an adverse effect on other properties. Structural modifications that improve the solubility of APIs usually increase toxicity and reduce permeability. Compared with chemical modification, physical modification is applicable to a wider group of APIs, is easier to prepare, and is usually the first choice of the industry. Among them, amorphization, cyclodextrin complexation, micronization, nano-sizing, and preparation of lipid-based preparations have been tried by researchers to modify ellagic acid. However, these methods require the addition of excipients and are complex processes, which limits their industrial scale-up. For example, nano-sizing usually needs to be prepared by precipitation, crystallization, high-pressure homogenization, wet grinding, and supercritical fluid. Summary of the invention

[0005] In view of the technical problem that ellagic acid has extremely low solubility and thus limits its application and development as an anti-aging agent, whitening agent or nutritional agent, the present invention provides an ellagic acid nanosuspension and its application which can improve the antioxidant, transdermal performance and oral bioavailability. The specific scheme is as follows:

[0006] An ellagic acid nanosuspension contains ellagic acid nanoparticles with a diameter of 100-1000 nm; the ellagic acid nanoparticles are composed of ellagic acid and a preparation solvent, and the preparation solvent is pure water or a mixed solution of an organic solvent and water. The organic solvent is selected from one or more of ethanol, propylene glycol, butylene glycol, and pentanediol, and the preferred ratio of the organic solvent to water is 0:1-3:1.

[0007] As an improvement of the present invention, the preparation solvent is water; the ellagic acid nanosuspension is prepared with water as the preparation solvent, and the solid obtained after drying has a composition of ellagic acid: water = 1:4 (molar ratio).

[0008] The ellagic acid nanosuspension is prepared by using a supersaturated ellagic acid solution through an ultrasonic process. The conditions of the ultrasonic process are preferably ellagic acid feed amount ≥ 20 mg / mL, and ultrasonic temperature ≥ 35°C, more preferably 45°C.

[0009] The present invention also provides the use of the ellagic acid nanosuspension in external preparations and oral preparations.

[0010] Beneficial Effects

[0011] The ellagic acid nanosuspension provided by the present invention can solve the solubility problem of ellagic acid (the equilibrium solubility is increased by more than 100 times) without adding a large amount of auxiliary materials or complicated preparation processes; at the same time, the antioxidant activity of the ellagic acid nanosuspension is significantly improved compared with its saturated aqueous solution (P<0.05), and is also significantly higher than the antioxidant activity of free ellagic acid at the same concentration (P<0.05). The former is because the solubility of the ellagic acid nanosuspension is greatly improved, and the latter may be closely related to its structural changes. The ellagic acid nanosuspension shows an antioxidant activity that is better than the same concentration of Vc. At the same time, after ellagic acid is prepared into a nanosuspension and administered transdermally, it not only increases the intradermal content, but also significantly increases the transdermal amount (P<0.05), which can enhance the local and systemic effects of ellagic acid; the ellagic acid nanosuspension can significantly increase the oral bioavailability of ellagic acid (4.69 times). The above comprehensive display ellagic acid nanosuspension in the field of topical preparations and oral development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Transmission electron microscopy images of ellagic acid nanosuspensions, wherein A-ultrapure water (1 μm), B-1.25% ethanol (1 μm), B-2.75% ethanol (1 μm), C-1.5% propylene glycol (500 nm), C-2.10% propylene glycol (500 nm), D-1.1% butylene glycol (1 μm), D-2.20% butylene glycol (500 nm), E-1.5% pentanediol (1 μm), E-2.10% pentanediol (2 μm), F-1.75% Ethanol (5μm), F-2.75% ethanol (2μm); the logo indicates the preparation solvent, such as "5% propylene glycol" indicates that the preparation solvent is 5% propylene glycol aqueous solution, and the scale is indicated in brackets; among them, groups A to E are TEM images of ellagic acid nanosuspensions, and group F is a TEM image of ellagic acid nanosuspension dried product after reconstitution, among which F-1.75% ethanol prepared ellagic acid nanosuspension dried product diluted with ultrapure water (5μm) and F-2. diluted with 1% butanediol (2μm)

[0013] Figure 2 Ultraviolet full wavelength scanning of ellagic acid nanosuspension before and after membrane rupture

[0014] Figure 3 Determination results of DPPH free radical scavenging rate (n=3)

[0015] Figure 4 Results of hydroxyl radical scavenging test (n=3)

[0016] Figure 5 Results of total reducing capacity determination (n=3)

[0017] Figure 6 Cumulative transdermal amount and intradermal retention (n=6)

[0018] Figure 7 Study on the preparation process of ellagic acid nanosuspension, including A. the effect of ellagic acid feed concentration; B. the effect of ultrasonic temperature

[0019] Figure 8 Characterization of ellagic acid nanosuspension, A. Macroscopic morphology of EA and EA NS; B. Saturated aqueous solution morphology of EA and EA NS; C. Tyndall effect of EA NS; D. Particle size distribution of EA NS; E. Particle size, potential, PDI, and pH value of EA NS before and after freeze-drying; F~J. Microscopic morphology of EA and EA NS, including F. Scanning electron microscopy of EA NS powder; G. Scanning electron microscopy of EA powder; H. Scanning electron microscopy of EANS solution; I. Scanning electron microscopy of EA solution; J. Transmission electron microscopy of EANS; K. UV full-wavelength scanning of EA NS aqueous suspension; L. Stability of EANS aqueous solution

[0020] Fig. 9 HPLC chart of ellagic acid nanosuspension freeze-dried powder solution

[0021] Fig.10 Specificity investigation: (A) blank plasma, (B) drug-containing plasma, and (C) plasma with ellagic acid as a reference substance Fig.11 Drug-time curves of ellagic acid (EA) and ellagic acid lyophilized nanosuspension (EA NS) (n=8)

[0022] Fig.12 Antioxidant activity test, (A) DPPH free radical scavenging activity (B) total reducing power (n=3)

[0023] Fig.13 UHPLC-MS / MS secondary mass spectrometry A. EA; B. EA hydrate; C. EA NS; D. Schematic diagram of ellagic acid cleavage law

[0024] Fig.14 Physical characterization A. Scanning calorimetry (DSC); B. Thermogravimetric analysis (TG); C. Fourier transform infrared spectroscopy (FTIR); DX-ray powder diffraction (XRPD)

[0025] In the figure, EA represents ellagic acid (CAS No.: 476-66-4), EA NS represents ellagic acid nanosuspension lyophilized powder, and EAHydrate represents ellagic acid hydrate (CAS No.: 314041-08-2); Figure 3-Figure 5In the figure, EA refers to ellagic acid group, EA nano refers to ellagic acid nanosuspension group, and the prefix "5% ethanol" is the preparation solvent of the ellagic acid nanosuspension; the meaning of * in the figure is: compared with the ellagic acid saturated aqueous solution group, *P<0.05, **P<0.01, ***P<0.001. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further described below in conjunction with specific examples, which are not intended to limit the technical scheme. Diols such as ethanol, propylene glycol, butylene glycol, and pentanediol are commonly used solvents, moisturizers, penetration enhancers, or preservatives in topical preparations or oral preparations. The most commonly used 1,3-propylene glycol, 1,3-butylene glycol, and 1,2-pentanediol are selected for testing in the following examples, but are not intended to limit the technical scheme.

[0027] The test samples in Examples 2 and 4-6 were all ellagic acid nanosuspensions prepared according to Example 1; the test sample in Example 8 was the ellagic acid nanosuspension prepared according to Example 7; and the test samples in Examples 10-14 were the ellagic acid nanosuspension freeze-dried powders prepared according to Example 9.

[0028] Example 1 Preparation of Ellagic Acid Nanosuspension

[0029] Excess ellagic acid powder is weighed, dissolved with pure water or a mixed solution of an organic solvent and water, and ultrasonically treated with an ultrasonic device under the following conditions: ultrasonic temperature ≥35°C, ultrasonic time ≥5min, ultrasonic power ≥100w, ultrasonic frequency ≥20kHz, the ultrasonic suspension is centrifuged at 3000-4000rpm for 10-40min, and then the solid part is removed, and the supernatant is taken to obtain the ellagic acid nanosuspension. The preferred embodiment is that the organic solvent is selected from one or more of ethanol, propylene glycol, butylene glycol, and pentanediol.

[0030] Example 2 Characterization of Ellagic Acid Nanosuspension - Morphology and Particle Size

[0031] Take the ellagic acid nanosuspension prepared in Example 1 (feeding amount is 500 μg ellagic acid / mL, ultrasonic conditions: ultrasonic temperature 45°C, ultrasonic time 60 min, ultrasonic power 450w, ultrasonic frequency 20kHz), take 10 μL of supernatant on the supported carbon film, absorb the solution on the carbon film after 5 minutes, use 10 μL of phosphotungstic acid to stain in the dark for 5 minutes, absorb the phosphotungstic acid, and use an infrared heating lamp to dry the solution on the carbon film. Use a transmission electron microscope TEM (Hitachi 7650 transmission electron microscope H-7650, or Hitachi 120kV transmission electron microscope HT7800, Hitachi, JP) to check the morphology of the particles and collect image analysis. The particle size and PDI of the solution are measured with a particle size analyzer, and the pH value is measured with a pH meter. The results are shown in Table 1. Combined with the TEM image ( Figure 1) The results show that ellagic acid nanosuspensions can be prepared using all solvents, and the nanoparticles are spherical in shape, but the preparation solvents have a certain influence on the morphology and particle size of the nanosuspensions.

[0032] Table 1 Particle size, PDI, and pH of ellagic acid nanosuspensions prepared in different solvents (n=3)

[0033]

[0034]

[0035] Example 3 Determination of ellagic acid concentration by ultraviolet spectrophotometry

[0036] Establishment of standard curve: accurately weigh 2.5 mg of ellagic acid standard in a 50 mL volumetric flask and dilute with methanol to prepare a 50 μg / mL standard solution for standby use. Then dilute with ethanol to obtain 12.5, 10, 6.25, 5, 3.125, 1.5625, 0.78125 μg / mL ellagic acid standard solutions, measure the absorbance value under ultraviolet wavelength of 254 nm, draw a standard curve with the mass concentration of ellagic acid standard solution as the abscissa (X) and the corresponding absorbance value (Y) as the ordinate, and perform linear regression on the standard curve to obtain the regression equation: Y = 0.0933X-0.0027, correlation coefficient R 2 =0.9999, indicating that ellagic acid has a good linear relationship in the range of 0.78125-12.5 μg / mL.

[0037] Concentration determination: The solution to be tested is completely dissolved by breaking the membrane with methanol, the 254nm UV absorbance is measured and substituted into the above-mentioned ellagic acid standard curve to calculate the concentration value, and the obtained concentration value is multiplied by the dilution factor to obtain the concentration of ellagic acid in the solution. Pay attention to the linear range during the test. If the ellagic acid concentration exceeds the linear range, further dilute it with methanol until it is within the linear range and then perform the UV test. The UV full wavelength scan of the ellagic acid nanosuspension (taking the ellagic acid nanosuspension prepared with 5% butanediol as an example) before and after the membrane is broken is shown in Figure 2 It can be seen that the curve obtained after membrane rupture has the ultraviolet characteristic absorption peaks of ellagic acid at 254nm and 366nm, while the absorption values ​​of ellagic acid nanosuspension (before membrane rupture) decrease at these two locations. At the same time, an absorption peak appears at 398nm (near visible light region), which shows that there is colloid in the solution at this time, which is assembled from free ellagic acid.

[0038] Example 4 Determination of saturation concentration of ellagic acid nanosuspension

[0039] The ellagic acid nanosuspension was prepared by the process in Example 1 (feeding amount was 500 μg ellagic acid / mL, ultrasonic conditions: ultrasonic temperature 45°C, ultrasonic time 60 min, ultrasonic power 450w, ultrasonic frequency 20kHz), and the saturated concentration of ellagic acid therein was determined by the method in Example 3. The results are shown in Table 2, and it can be seen that the saturated concentration of ellagic acid can be significantly improved after ellagic acid is prepared into a nanosuspension using different solvents.

[0040] Table 2 Saturation concentration of ellagic acid nanosuspensions prepared by different solvents

[0041]

[0042] Example 5 Evaluation of Antioxidant Performance of Ellagic Acid Nanosuspension

[0043] 1. Solution Preparation

[0044] (1) Preparation of ellagic acid nanosuspension: 10 mg of ellagic acid standard was accurately measured and diluted to a 25 mL volumetric flask with 5%, 25%, and 75% ethanol, respectively. The suspension was ultrasonicated at 45°C for 60 min (ultrasonic power and frequency 500 w, 45 kHz), centrifuged at 4000 rpm for 40 min, and the supernatant was collected to obtain the sample to be tested.

[0045] (2) Preparation of free ellagic acid solution (positive control) of the same concentration in each group: The ellagic acid of the same concentration in each group in (1) was completely dissolved in the ethanol solution. At this time, the ellagic acid had no nanostructure and existed in a free form. The preparation method was as follows: Using the ellagic acid concentration measured in each group in (1) as the standard, 100% ethanol was used as the solvent to prepare the corresponding control solution. The UV full wavelength scanning images of groups (1) and (2) were compared with Figure 2 The results are consistent before and after membrane disruption, proving that the ellagic acid in group (2) exists in a free form, that is, in a fully membrane-disrupted state, while the solution in group (1) contains a large amount of ellagic acid nanosuspension.

[0046] (3) Preparation of saturated aqueous solution of ellagic acid (negative control): (ellagic acid exists in free form)

[0047] Accurately weigh 10 mg of ellagic acid standard, dilute to volume with distilled water in a 25 mL volumetric flask, shake well to fully dissolve it, centrifuge at 12000 rpm for 10 min, take the supernatant, and obtain the sample to be tested.

[0048] (4)V c Preparation of control solution: Select recognized antioxidant V c As a positive drug, the concentration is always selected to be consistent with the ellagic acid concentration in the ellagic acid nanosuspension prepared by 75% ethanol (because the ellagic acid content is the highest under the preparation solvent conditions), and it is dissolved in ethanol.

[0049] The ellagic acid content in the solutions of (1), (2) and (3) was determined by the method in Example 3. The drug content in each group is shown in Table 3.

[0050] Table 3 The content of ellagic acid in ellagic acid nanosuspensions prepared by different solvents

[0051]

[0052] 2. DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging rate test

[0053] Take 1mL of the test solution and add it to a 5mL centrifuge tube. Then add 1mL of a 200μg / mL DPPH solution freshly prepared with anhydrous ethanol to each tube. Finally, add 1mL of the corresponding solvent, mix well, place at room temperature and avoid light for 30min, centrifuge at 3000rpm for 10min, and measure by ultraviolet at 517nm. The DPPH free radical scavenging rate is calculated using the formula:

[0054]

[0055] The absorbance determination method of A1, A2, and A0 is shown in Table 4:

[0056] Table 4 DPPH free radical scavenging test sample addition table

[0057]

[0058] The experimental results are shown in Figure 3 The DPPH free radical scavenging rates of the ellagic acid nanosuspensions prepared with 5, 25, and 75% ethanol were all higher, significantly stronger than those of the ellagic acid saturated solution group and the free ellagic acid group with the same concentration. c Groups are close.

[0059] 3. Hydroxyl radical scavenging test

[0060] 1 mL of sample, 1 mL of 1.5 mmoL / L o-phenanthroline, 2 mL of pH 7.4 PBS buffer, 1 mL of 1.5 mmoL / L ferrous sulfate, and 1 mL of hydrogen peroxide (volume fraction 0.01%) were added to the test tube in sequence. The test tube was then placed in a 37°C water bath for 60 min, and the absorbance value A1 of each group was measured at 510 nm. The absorbance value A0 was measured by replacing the sample solution with 1 mL of solvent and hydrogen peroxide with 1 mL of distilled water, and the absorbance value A2 was measured by replacing the sample solution with 1 mL of solvent. The hydroxyl radical scavenging rate was calculated by the following formula:

[0061] In the formula, the absorbance determination method of A1, A2, and A0 is shown in Table 5:

[0062] Table 5 Hydroxyl free radical scavenging test sample addition table

[0063]

[0064]

[0065] The experimental results are shown in Figure 4 , the hydroxyl radical scavenging rate of ellagic acid saturated aqueous solution is extremely low, while the hydroxyl radical scavenging rate of ellagic acid nanosuspension group prepared with 5, 25, and 75% ethanol increases with the increase of ethanol content in the preparation solvent, which is consistent with the trend of increasing saturated concentration of ellagic acid. At the same time, the hydroxyl radical scavenging rate of the nanosuspension group is significantly higher than that of the saturated aqueous solution group (P<0.01), significantly higher than that of the Vc control group (P<0.01), and significantly higher than that of the ellagic acid free group with the same concentration (P<0.05). The above experiments show that although the scavenging rate of Vc for hydroxyl radicals is better than that of ellagic acid saturated aqueous solution, after the solubility is improved by the nanosuspension preparation process, the scavenging effect of ellagic acid on hydroxyl radicals is much better than that of the positive drug Vc at the same concentration, indicating the excellent antioxidant capacity of ellagic acid.

[0066] 3. Total reducing power test

[0067] Fe 3+ The test method of reducing power is as follows: take 1mL sample and mix it with 2mL pH7.4 PBS buffer and 1mL 2% potassium ferricyanide solution, react at 50℃ for 30min, cool rapidly in ice water, add 2.5mL 10% trichloroacetic acid, centrifuge at 3500r / min for 10min, take 2mL supernatant and mix with 2mL distilled water and 0.5mL 0.1% ferric chloride, mix evenly, measure the absorbance value A1 at 700nm, and measure the absorbance value A2 with 0.5mL distilled water instead of ferric chloride (see Table 6). The reducing power is represented by the difference between A1 and A2. The larger the difference, the greater the reducing power.

[0068] Table 6 Total reducing capacity test sample addition table

[0069]

[0070] The experimental results are shown in Figure 5, similar to the results of hydroxyl radical scavenging rate, the total reducing power of ellagic acid saturated aqueous solution is low, while the total reducing power of ellagic acid nanosuspension groups prepared with 5, 25, and 75% ethanol increases with the increase of ethanol content in the preparation solvent, which is consistent with the trend of increasing saturated concentration of ellagic acid. At the same time, the total reducing power of the nanosuspension group is significantly higher than that of the saturated aqueous solution group (P<0.001), significantly higher than the Vc control group at the same concentration (P<0.05), and significantly higher than the ellagic acid free group at the same concentration (P<0.05). The above experiments show that although the total reducing power of Vc is stronger than that of ellagic acid saturated aqueous solution, after the solubility is improved by the nanosuspension preparation process, the total reducing power of ellagic acid is better than that of the positive drug Vc, indicating the excellent antioxidant ability of ellagic acid.

[0071] The antioxidant performance test results in this embodiment jointly show that ellagic acid has excellent antioxidant capacity, which is higher than Vc at the same concentration, and its extremely low solubility limits the expression of its antioxidant capacity. The ellagic acid nanosuspension preparation process described in Example 1 can solve the solubility problem (Example 4), thereby improving the antioxidant effect; surprisingly, the antioxidant effect of ellagic acid nanosuspension is even better than that of ellagic acid free group at the same concentration, indicating that ellagic acid can not only increase its efficacy due to the improvement of solubility through the nano preparation process described in Example 1, but also the structure itself has a significant effect on the efficacy. At this time, the solvent is a mixed solvent of an organic solvent and water, which is suitable for multiple application scenarios such as oral, external, and injection. At the same time, the morphology of the nanosuspension (Example 2) and the saturation concentration (Example 4) can be adjusted by adjusting the type and ratio of the preparation solvent to adapt to different application scenarios. The above experimental results comprehensively show the application prospects of ellagic acid nanosuspension.

[0072] Example 6 Investigation of Transdermal Absorption Performance of Ellagic Acid Nanosuspension

[0073] 1. Sample Preparation

[0074] The experiment was divided into an ellagic acid nanosuspension group and a free group (control), wherein the preparation method of the free group was the same as the preparation method of the ellagic acid saturated aqueous solution under "1. (3)" in Example 5, except that the solvent at this time was 5% butylene glycol; the ellagic acid nanosuspension group selected 75% ethanol as the preparation solvent, and the method was the same as "1. (1)" in Example 5. The obtained ellagic acid nanosuspension was prepared by the method in Example 1 to obtain an ellagic acid nanosuspension, and was dissolved with 5% butylene glycol to a concentration similar to that of the free group before use. The two groups selected 5% butylene glycol to maintain the consistency of the solvent, and butylene glycol has a certain penetration-promoting effect, which is beneficial to the transdermal absorption of drugs, is commonly used in external preparations, and is also a common solvent and moisturizer in cosmetics. After the test solution was prepared, the ellagic acid content of each group was measured by the method in Example 3, and other parameters were listed in Table 7.

[0075] Table 7 Parameters of the two ellagic acid administration groups

[0076]

[0077] 2. HPLC determination of ellagic acid content

[0078] 2.1 HPLC conditions

[0079] Chromatographic column: H ellagic acid era C18 column (4.6mm×250.0mm, 5μm); mobile phase: acetonitrile-phosphoric acid (V 乙腈 :V 磷酸 =20:80, the volume fraction of phosphoric acid is 0.2%), the detection wavelength is 254nm; the flow rate is 0.80mL / min, and the injection volume is 15μL.

[0080] 2.2 Preparation of standard curve

[0081] 1.0 mg of ellagic acid was accurately weighed, dissolved in methanol and fixed to volume in a 50 mL volumetric flask to prepare a 20 μg / mL ellagic acid reference substance mother solution. The mother solution was diluted to obtain a series of reference substance solutions with mass concentrations of 0.05, 0.1, 0.5, 1, 2, 5, and 10 μg / mL, respectively. The samples were injected for analysis, and the peak area of ​​ellagic acid was determined as the ordinate (Y). The mass concentration of ellagic acid was used as the abscissa (X). Linear regression was performed to obtain the linear regression equation Y=127670X-108.15, and the correlation coefficient R 2 =0.9999 line, and the linear range is 0.05~10μg / mL.

[0082] 3. Transdermal test

[0083] 3.1 Preparation of ex vivo mouse skin

[0084] SD male rats were anesthetized with 10% chloral hydrate, and the abdominal hair was shaved with a razor blade. The rats were killed by dislocating the neck the next day, and the intact abdominal skin was obtained. The subcutaneous adipose tissue was removed with tweezers, and the treated skin was cleaned with pH 7.4 PBS solution, dried with filter paper, flattened, wrapped with filter paper, and stored in a -80°C refrigerator. It was thawed with pH 7.4 PBS solution 40 minutes before use.

[0085] 3.2 Transdermal test

[0086] Franz diffusion cell method was used. The mouse skin stratum corneum was fixed upward between the receiving chamber and the donor chamber. The diffusion cell area was 3.14 cm 2 , volume 8mL, in order to facilitate direct high performance liquid chromatography determination, methanol: physiological saline = 50:50 (v / v) as the receiving liquid, the temperature was controlled at (37.0±0.5)℃, the speed was 400r·min-1 1 mL of drug solution was added to the supply chamber, and 0.2 mL of receiving solution was taken out at 0.5, 1, 3, 9, 12, 18, and 24 h, and 0.2 mL of new receiving solution was added. Centrifugation was performed at 12000 rpm for 10 min, and 150 μL of supernatant was taken for HPLC analysis to calculate the cumulative transdermal amount Q n And record the results, Q n The calculation formula is as follows:

[0087]

[0088] Where: V t is the volume of the receiving pool; ρ n is the mass concentration of the nth sampling point; ρ n-1 is the mass concentration of the n-1th sampling point; V s is the sampling volume each time; S0 is the penetration area.

[0089] After the experiment, the mouse skin was removed, the residual drugs on the surface were rinsed off, the skin at the transdermal site was taken, cut into pieces, and homogenized with 1.0 mL of methanol. The homogenate was transferred to a 2 mL centrifuge tube, ultrasonicated at 50 kHz for 20 min, and centrifuged at 12000 rpm for 10 min. The supernatant was taken for chromatographic analysis to calculate the content of ellagic acid in the skin, that is, the intradermal retention amount.

[0090] The results of the cumulative amount of ellagic acid permeated through the skin and the amount of intradermal retention are shown in Figure 6 It can be seen that after ellagic acid is prepared into a nanosuspension and administered percutaneously, its retention in the skin is significantly increased compared with that of free ellagic acid. At the same time, the cumulative transdermal amount of ellagic acid in the nanosuspension group is twice that of the free group, which is statistically significant (P<0.05); this shows that the use of ellagic acid nanosuspension in topical preparations can not only significantly increase the intradermal content of ellagic acid, but also significantly increase the transdermal amount, and enhance the local and systemic effects of ellagic acid. Combined with the test of the antioxidant properties in Example 5, it shows the development prospects of ellagic acid nanosuspension in the field of topical preparations, especially in the field of cosmetics.

[0091] Example 7 Preparation of Ellagic Acid Nanosuspension

[0092] Different from Example 1, the supersaturated ellagic acid solution is subjected to ultrasonic treatment twice, using an ultrasonic cleaner and an ultrasonic disruptor. The purpose of further ultrasonic treatment with the ultrasonic disruptor is to improve the formation efficiency of ellagic acid nanoparticles and reduce the particle size of the nanoparticles.

[0093] The preparation method of the ellagic acid nanosuspension used in the experiments of Examples 8-14 is as follows: take excess ellagic acid, prepare the suspension with ultrapure water, shake and mix, then place it in an ultrasonic cleaner at 45°C for 60 minutes, then use an ultrasonic cell disruptor for 2 minutes, place the probe 3 cm below the liquid, the condition is 50% power (450W), the ultrasound is turned on for 2 seconds and off for 2 seconds. After the ultrasound is completed, place it in a 10mL centrifuge tube, centrifuge at 4000rpm for 16 minutes, take the supernatant, and obtain the ellagic acid nanosuspension (EA NS).

[0094] Example 8 Optimization of Preparation Conditions of Ellagic Acid Nanosuspension

[0095] (1) Investigation of ellagic acid dosage

[0096] The results of preliminary experiments show that the dosage of ellagic acid is a key parameter in the preparation of ellagic acid nanosuspension. The dosage is not enough to reach supersaturation. Increasing the dosage under supersaturation can further increase the solubility of ellagic acid. Therefore, the experiment is designed as follows: 25, 50, 100, 200, 300, and 400 mg of ellagic acid are weighed in a 10 mL centrifuge tube, and ultrapure water is added to the 10 mL mark to obtain 2.5, 5, 10, 20, 30, and 40 mg / mL of the prepared mixed solution. The ellagic acid nanosuspension was prepared by the method in Example 7 (ultrasonic conditions: ultrasonic temperature 45°C, ultrasonic time 60 min, ultrasonic power 450w, ultrasonic frequency 20kHz), and the ellagic acid concentration was determined by the method in Example 3. Figure 7 -A shows that the feed amount has a great influence on the concentration of ellagic acid in the nanosuspension. In the range of 2.5-20 mg / mL, the larger the feed amount during preparation, the greater the ellagic acid concentration. After exceeding this point, the concentration decreases and a large amount of ellagic acid API precipitation is observed. Therefore, a feed amount of 20 mg / mL was selected for the preparation of ellagic acid nanosuspension.

[0097] (2) Ultrasonic temperature investigation

[0098] Six portions of 200 mg ellagic acid were placed in 10 mL centrifuge tubes to prepare a 20 mg / mL ellagic acid mixture. The ellagic acid nanosuspension was prepared by ultrasonic treatment at 30, 35, 40, 45, 50, and 55 °C according to the method in (1). The ellagic acid concentration was determined by the method in Example 3. Figure 7 -B shows that as the ultrasonic temperature increases, the concentration of ellagic acid in the ellagic acid nanosuspension increases continuously, reaches a peak at 45°C, and then remains basically unchanged. Therefore, an ultrasonic temperature of 45°C was selected for the preparation of the ellagic acid nanosuspension.

[0099] (3) Ultrasound frequency investigation

[0100] Take 200mg of ellagic acid in a 10mL centrifuge tube and prepare a 20mg / mL ellagic acid suspension. Prepare ellagic acid nanosuspension by ultrasonic method (1) at 45°C ultrasonic temperature. Add ultrapure water of equal amount to the precipitate after centrifugation, prepare by ultrasonic method again, and repeat several times. The ellagic acid nanosuspension prepared each time is measured by the method in Example 3, and the particle size and PDI are measured by a particle size analyzer. The results in Table 8 show that with the increase of the number of ultrasonic times, the ellagic acid concentration in the ellagic acid nanosuspension decreases successively, which may be because the total concentration of ellagic acid in the prepared solution decreases after each supernatant is taken out. However, after 7 ultrasonic times, the ellagic acid concentration can still reach 1.20mg / mL, indicating that the residual ellagic acid solid prepared can be reused many times. At the same time, according to the particle size measurement results, the number of ultrasonic times within 3 times has no effect on the particle size, and then the particle size gradually increases with the increase of the number of ultrasonic times. In addition, the PDI of each group of ultrasonic times is small, and the particle size distribution is uniform. The above results show that multiple ultrasound treatments can still produce ellagic acid nanosuspensions with relatively high concentrations, which supports the reuse of raw materials.

[0101] Table 8 Ultrasound times investigated (n=3)

[0102]

[0103]

[0104] The above experimental results comprehensively show that, with ellagic acid saturation concentration as the evaluation index, the optimal preparation process of ellagic acid nanosuspension is a feed amount of 20 mg / mL, an ultrasonic temperature of 45°C, and the ellagic acid raw material can be reused for multiple ultrasonic treatments. At the same time, according to the preliminary experimental results, extending the ultrasonic time, increasing the ultrasonic power or frequency can further increase the saturation concentration of ellagic acid. Therefore, the saturation concentration of ellagic acid nanosuspension can be adjusted by adjusting these variables to meet the needs of different application scenarios.

[0105] Example 9 Preparation of dried ellagic acid nanosuspension

[0106] The ellagic acid nanosuspension is dried and solidified by any of the following two methods: Method ① Rotary evaporation method: The preferred method is as follows: the ellagic acid nanosuspension is rotary evaporated at 50°C to obtain a solid, dried at 50°C until completely dry, and the solid is scraped to obtain the ellagic acid nanosuspension dry product. Method ② Vacuum freeze drying method: The preferred method is as follows: the ellagic acid nanosuspension is poured into a glass dish, pre-frozen at -50°C for 6h, and freeze-dried at -40°C to 25°C for 28h according to the freeze drying process in Table 9 to obtain the ellagic acid nanosuspension freeze-dried powder.

[0107] Table 9 Freeze-drying process

[0108]

[0109] The test samples in Examples 10-14 are freeze-dried powders of ellagic acid nanosuspension obtained by the vacuum freeze-drying method in this example, hereinafter referred to as EA NS.

[0110] Example 10 Characterization of Ellagic Acid Nanosuspension Lyophilized Powder (EA NS)

[0111] 1. Scanning electron microscopy (FESEM-EDS test)

[0112] EA and EANS were tested as powder samples or dissolved in ethanol. FESEM images and EDS quantification were collected using TESCANMAIA3 GMU and energy dispersive X-ray (EDX) spectroscopy (OXFORDULTIM MAX 170). Samples were imaged using backscattered (BSE) or secondary electron (SE) detectors at an accelerating voltage of 5-20 keV.

[0113] 2. Transmission Electron Microscope (TEM)

[0114] The method is the same as in Example 2.

[0115] 3. Determination of particle size, potential and PDI

[0116] After taking the sample and diluting it with an appropriate amount of ultrapure water, the particle size, PDI and Zeta potential information were measured using a particle size analyzer, and each measurement was repeated three times.

[0117] 4. Ultraviolet (UV)-Visible Spectroscopy

[0118] EA NS solution (0.1 mg / mL) was prepared in ultrapure water. The UV-vis spectra of EANS were recorded from 190 to 320 nm at room temperature (25°C) using a UV-vis spectrophotometer UV-2700 (Shimadzu, Kyoto, Japan).

[0119] 5. Content Determination

[0120] The EA content in the EA NS powder was determined using the method of Example 3 “Determination of ellagic acid concentration by ultraviolet spectrophotometry”.

[0121] 6. Elemental analysis

[0122] Thermo elemental analyzer was used to analyze the element distribution in EN NS freeze-dried powder. Helium and oxygen were turned on, and the pressure was adjusted to He: 0.12MPa; O2: 0.20MPa; the operation mode was selected as CHNS, and the pressure was adjusted to He: 0.12MPa; O2: 0.20MPa, and the sample was added. When the content of C, H, N, and S elements was stable, the analysis was stopped and the data was read.

[0123] The experimental results are summarized as follows: During pre-freezing, the eutectic point of ellagic acid nanosuspension detected by electrical resistance method was -1.7℃. Figure 8 It can be seen that in terms of macroscopic morphology, the structure of EA powder is dense, while the structure of EANS powder is loose and has a sponge-like structure ( Figure 8 -A); when saturated with water, the color of EA NS is observed to be dark ( Figure 8 -B). Scanning electron microscopy results showed that EANS powder ( Figure 8 -F) and solution ( Figure 8 -H) state, they all showed rod-like nanostructures (Nanoparticles, NPs), and the size of them in solution was measured by a particle size analyzer to be 147.3±0.73nm ( Figure 8 -D / E), while EA in powder ( Figure 8 -G) or solution ( Figure 8 -I) state, the structure was not observed; transmission electron microscopy ( Figure 8 -J) also observed the rod-like nanostructure of EA NS, but it was composed of spherical nanoparticles at both ends. It is speculated that the formation process of the rod-like nanostructure is that EA self-assembles into spherical nanoparticles after ultrasonic treatment ( Figure 1 ), and then freeze-dried in vacuum to form rods ( Figure 8 -F / H / J), both of which are nanosized structures. After dilution with water, the EA NS powder showed a significant Tyndall effect and uniform particle size distribution (PDI was about 0.2) ( Figure 8 -E / C). The UV full wavelength scanning results further confirmed the formation of nanoparticles. Compared with the UV absorption spectrum of ellagic acid (characteristic absorption peaks at 254nm and 366nm), EA NS produced an obvious absorption peak at 398nm (near visible light region) ( Figure 8 -K), and previous studies have shown that this peak disappears after dilution with methanol and membrane breaking ( Figure 2 ), restored to the standard spectrum of ellagic acid free sample.

[0124] at the same time, Figure 8-E also showed that the ultrasound process was a key step in the formation of ellagic acid NPs, and the freeze-drying process slightly increased the size of the NPs without changing their Zeta potential or pH. In addition, EA NSs have a strong negative charge on the surface (about -42 mV), which may contribute to the stability of the solution. In addition, the change in particle size of EA NSs dissolved in water showed that the solution stability within 7 days ( Figure 8 -L).

[0125] Finally, the content of EA in the 6 batches of EA NS freeze-dried powder was determined (Table 10), and the drug loading was 80.11±0.65%; at the same time, the EA NS freeze-dried powder was analyzed for four elements, C, H, N, and O, and the results are shown in Table 11. The "mass percentage" line in the analysis results was converted to a molar percentage of C:H:O=1.17:1.21:1. Since the molecular formulas of EA and H2O are C14H6O8 and H2O, respectively, the EA:water in the EA NS freeze-dried powder is converted to 1:4 (molar ratio). When converted to mass percentage, the EA content is 80.74%, which is basically consistent with the above content test results, indicating that the material composition of EA NS is EA:water≈1:4 (molar composition), which is credible.

[0126] Table 10 Drug loading (n=6)

[0127]

[0128]

[0129] Table 11 Elemental analysis results of EA NS lyophilized powder (n=6)

[0130]

[0131] Example 11 Equilibrium Solubility Study

[0132] 1. Determination of ellagic acid content by HPLC

[0133] 1.1 Chromatographic conditions: The chromatographic column was Hedera C18 column (250 mm × 4.6 mm, 5 μm), and the mobile phase was acetonitrile-0.2% phosphoric acid aqueous solution (V 乙腈 :V 磷酸 =20:80), flow rate 1.0 mL / min, detection wavelength 254 nm, column temperature 30 °C, injection volume 10 μL, spectrum acquisition time 15 min.

[0134] 1.2 Investigation of linear relationship The reference solution was prepared into a 100 μg / mL stock solution, which was diluted with methanol to 100, 50, 25, 12.5, 6.25, 3.125, 1.5625, 0.78125, 0.390625, and 0.1953125 μg / mL, and injected into HPLC. The standard curve (Y) was established with the mass concentration of the ellagic acid reference solution as the abscissa (X) and the corresponding peak area as the ordinate. The result was Y=1.5937X+0.4033, R2=0.9992, and the linear range was 0.1953125-100 μg / mL.

[0135] 1.3 Precision Investigation A 25 μg / mL ellagic acid nanosuspension freeze-dried powder aqueous solution (test sample) was prepared and sampled 6 times continuously to determine its peak area and calculate the relative standard deviation RSD. The peak area RSD was 0.69%, indicating that the instrument had good precision.

[0136] 1.4 Stability Study Prepare the same test solution as above, inject once at 0, 4, 8, 12, 24, and 48 hours, measure the peak area and calculate the relative standard deviation RSD. The peak area RSD is 1.80%, indicating that the test solution is stable for 48 hours.

[0137] 1.5 Repeatability Study Six samples of the same concentration were prepared and injected six times. The peak area was determined and the concentration and relative standard deviation (RSD) were calculated based on the standard curve. The concentration of the six samples was (54.83±2.61) μg / mL, with an RSD of 3.20%, indicating that the method had good repeatability.

[0138] 1.6 Sample recovery rate investigation Weigh 6 samples of EA NS freeze-dried powder with determined ellagic acid content accurately, 10 mg each, add an appropriate amount of reference substance to the same amount as ellagic acid in the sample, 8.01 mg, prepare the test solution, determine the peak area and calculate the mass concentration, calculate the average sample recovery rate and its RSD. The average sample recovery rate was 97.28%, and the RSD was 0.93%. According to the requirements of the 2020 edition of the General Principles 9101 of the Validation of Analytical Methods for Drug Quality Standards of the Chinese Pharmacopoeia, the sample recovery rate of ellagic acid meets the requirements of the pharmacopoeia.

[0139] 1.7 System suitability investigation HPLC chromatogram is shown in Fig. 9 The theoretical plate number of ellagic acid is 12565. It can be seen that the ellagic acid peak has no interference and the separation is good, indicating that the method has good specificity.

[0140] 2. Equilibrium Solubility Determination

[0141] Excess ellagic acid and EA NS lyophilized powder were separately added into 10 mL centrifuge tubes, and then 3 mL of solvent was added. After sealing with a sealing film, the tubes were placed in a 37 °C constant temperature water bath and shaken for 24 h, with 3 parallel samples. After stopping shaking and standing at 37 °C for 1 h, the supernatant was taken for separation. Since ellagic acid nanoparticles exist in the solution in a suspended manner, the separation method will seriously affect the measured value of its equilibrium solubility. Two separation methods were established respectively: ① passing through a 0.45 μm membrane; ② taking the supernatant after free sedimentation for 48 h. Immediately after separation, methanol was added for dilution to obtain the sample to be measured, which was reserved. The total concentration of ellagic acid in the sample to be measured was determined by HPLC, which was the equilibrium solubility.

[0142] To investigate the equilibrium solubility of EA NS in different solvents, the above-mentioned solvents were selected as water, normal saline, and methanol; according to the basic requirements for the determination of equilibrium solubility, the equilibrium solubility under different pH conditions was further investigated. The above-mentioned solvents were selected as buffer solutions with pH 1.2, pH 4.5, and pH 6.8 to simulate the existence state in gastric juice and intestinal juice.

[0143] Table 12 shows the equilibrium solubility of EA NS lyophilized powder in different solvents (water, normal saline, and methanol). It can be seen that the solubility of free ellagic acid in water is extremely low, while that of EA NS increases significantly. The data measured by the two separation methods increased by 100 - 120 times, up to 1395.58 ± 211.45 μg / mL at the highest. At the same time, the solubility of free ellagic acid in methanol is relatively large, and that of the EA NS lyophilized powder group is even larger, achieving 1.6 - 2.5 times, up to 2360.97 ± 65.12 μg / mL at the highest. Finally, no dissolved substances were detected in the two ellagic acid solutions in normal saline. This may be because the water solubility of ellagic acid benefits from the combination of phenolic hydroxyl groups with water, and the participation of salts in the solution will compete for this binding effect, ultimately leading to the precipitation of ellagic acid. This phenomenon is similar to the salting-out ion effect of adding salts to proteins and is common in polyphenols. After preparing ellagic acid into nanoparticles, the phenolic hydroxyl groups on its surface produce the same effect. Therefore, the strategy of ellagic acid nano-suspension cannot change the disadvantage that ellagic acid is insoluble in normal saline.

[0144] At the same time, Table 12 shows the equilibrium solubility of EA NS lyophilized powder under different pH conditions (buffer solutions with pH 1.2, pH 4.5, and pH 6.8). It can be seen that both ellagic acid solutions can hardly dissolve under the condition of pH 1.2. This may be because at this time pH < pKa, ellagic acid exists in a molecular state, and the dissolution condition of the molecular state is much lower than that of the ionic state. It is also possible that the self-assembly of ellagic acid nanoparticles relies on intermolecular hydrogen bonds, and under acidic conditions, H +Competition for this binding relationship leads to the deconstruction of the nanoparticles. This situation was significantly improved with the increase in pH. At pH 4.5, the free ellagic acid group was still almost insoluble, but the solubility of the ellagic acid nanosuspension group was significantly improved, with an increase rate of up to 2761.5 times after free sedimentation separation. At pH 6.8, the solubility of free ellagic acid increased, but it was still small. The equilibrium solubility of the EA NS freeze-dried powder group was significantly improved, reaching 547.71±149.68μg / mL after membrane separation.

[0145] Table 12 Equilibrium solubility investigation (n=3)

[0146]

[0147] Note: ND stands for “Not D e t ec t e d", not detected; *P<0.5, **P<0.1, ***P<0.001 compared with ellagic acid

[0148] Example 12 Oral bioavailability study

[0149] 1. Investigation of recovery rate of plasma treatment method

[0150] Use acetonitrile to precipitate the protein in the plasma. The processing steps are as follows: take out the blank plasma stored in -20℃, melt it in a 37℃ water bath, take 90μL and add 10μL 25mg / mL ellagic acid reference substance, vortex for 1min, add 190μL phosphate buffer (KH2PO4: 50% H2PO4, 175: 15) and vortex for 1min, then add 700μL acetonitrile (containing 0.1% formic acid) and vortex for 5min, refrigerate at 4℃ to precipitate protein for 30min, centrifuge at 4℃ 8000rpm for 5min, and transfer the supernatant. Add 300μL acetonitrile (containing 0.1% formic acid) to the precipitate for washing, vortex for 3min, centrifuge at 4℃ 8000rpm for 5min, and combine the supernatants of the two times. The supernatant was evaporated at 30°C using a refrigerated centrifugal concentrator, methanol was added to the centrifuge tube of the dried sample for reconstitution, ultrasonication was performed for 10 seconds, and centrifugation was performed at 12000 rpm at 4°C for 10 minutes. The supernatant was taken for HPLC analysis.

[0151] Calculate the recovery rate (%) based on the HPLC analysis results = measured peak area / reference peak area × 100%

[0152] The experimental results showed that the recovery rate of protein precipitation method was as high as 97.94±1.43%, RSD1.46%, indicating that the plasma treatment method has high drug extraction efficiency and good stability. The plasma sample treatment method was determined as follows: take out the plasma stored in -20℃ freezer, melt it in a 37℃ water bath, take 90μL and add 190μL phosphate buffer (KH2PO4: 50% H2PO4, 175: 15) and vortex for 1min, then add 700μL acetonitrile (containing 0.1% formic acid) and vortex for 5min, refrigerate at 4℃ to precipitate protein for 30min, centrifuge at 4℃ 8000rpm for 5min, and transfer the supernatant. Add 300μL acetonitrile (containing 0.1% formic acid) to the precipitate for washing, vortex for 3min, centrifuge at 4℃ 8000rpm for 5min, and combine the supernatants of the two times. The supernatant was evaporated at 30°C using a refrigerated centrifugal concentrator, methanol was added to the centrifuge tube of the dried sample for reconstitution, ultrasonication was performed for 10 seconds, and centrifugation was performed at 12000 rpm at 4°C for 10 minutes. The supernatant was injected into HPLC for component analysis.

[0153] 2.HPLC content analysis

[0154] 2.1 Chromatographic conditions: Chromatographic column: Hedera C18 column (250 mm × 4.6 mm, 5 μm), mobile phase: acetonitrile-0.2% phosphoric acid aqueous solution (V 乙腈 :V 磷酸 =20:80), flow rate 1.0 mL / min, detection wavelength 254 nm, column temperature 30 °C, injection volume 15 μL, and spectrum acquisition time 15 min.

[0155] 2.2 Investigation of linear relationship: Take the ellagic acid reference substance stock solution, dilute it with methanol to 32, 16, 8, 4, 2, 1, 0.5 μg / mL, treat the plasma sample according to the method in "Example 12 1", and perform HPLC injection analysis. Use the mass concentration of the solution as the abscissa (X) and the ellagic acid peak area as the ordinate (Y) for linear regression to establish a standard curve, which is Y=0.0017X+0.0661, R2=0.9998, and the linear range is 40-3200 ng / mL. Gradually dilute the ellagic acid reference substance stock solution for injection, and the detection limit is 10 ng / mL according to the concentration at the signal-to-noise ratio of 3:1 (0.033 mAU), and the quantification limit is 26 ng / mL according to the concentration at the signal-to-noise ratio of 10:1 (0.11 mAU).

[0156] 2.3 Methodological investigation: Method validation was performed with reference to the "Guidelines for Validation of Analytical Methods in Part IV of the Chinese Pharmacopoeia 2020 Edition 9101" and "Guidelines for Validation of Quantitative Analysis Methods for Biological Samples in Part IV of the Chinese Pharmacopoeia 2020 Edition 9012": ① Selectivity: Blank plasma, drug-containing plasma, and plasma with ellagic acid reference stock solution were treated according to the method in "Example 12, 1" and then sampled and analyzed. The HPLC chart showed that the retention time of ellagic acid was 9.108 min, and the resolution was greater than 1.5, which could distinguish ellagic acid from other components ( Fig.10 ), indicating that the method has high specificity.

[0157] ② Accuracy: Intra-batch accuracy: Take the ellagic acid reference stock solution, dilute it with methanol to 4 concentrations of high (16ug / mL), medium (4ug / mL), low (1ug / mL) and lower limit of quantitation (0.5ug / mL), process it according to the method in 2.1, and then inject and analyze it. For each concentration, take 5 samples, and calculate the accuracy according to (measured value / true value)×100%. Inter-batch accuracy: Repeat the intra-batch accuracy determination method to process 3 batches of samples, process and inject and analyze them in 2 days, and calculate the accuracy according to (measured value / true value)×100%. The results are as follows: the intra-batch accuracy at high (16 μg / mL), medium (4 μg / mL), low (1 μg / mL) and lower limit of quantitation (0.5 μg / mL) was 86.76%, 86.63%, 92.49%, 97.74%, respectively, and the inter-batch accuracy was 85.66%, 89.83%, 89.89%, 91.56%, respectively. The mean accuracy was within ±15%, and the method had good accuracy.

[0158] ③ Precision: Calculate the relative standard deviation RSD of the above accuracy samples, which is the relative standard deviation RSD of intra-batch precision and inter-batch precision. The intra-batch precision at high (16μg / mL), medium (4μg / mL), low (1μg / mL) and lower limit of quantification (0.5μg / mL) is 86.76%, 86.63%, 92.49%, 97.74%, respectively, and the inter-batch precision is 85.66%, 89.83%, 89.89%, 91.56%, respectively. The mean precision is within ±15%, and the precision is good.

[0159] ④Stability: Take the ellagic acid reference stock solution, dilute it to high (16μg / mL), medium (4μg / mL), and low (1μg / mL) with methanol, and process it according to the method in 2.1. Take 5 samples for each concentration, and analyze them by HPLC injection at 0, 4, 8, 24, and 48 hours, and calculate the RSD of each concentration. The samples are always placed in the autosampler to investigate the stability of the treated plasma samples under the experimental storage conditions (-4°C) and the autosampler temperature (10°C). The results are as follows: The RSD of the high, medium, and low concentration samples is calculated to be 0.64%, 1.17%, and 1.65%, indicating that the samples are stable for 48 hours under the storage conditions (-4°C) and the autosampler temperature (-10°C).

[0160] 3. Grouping, medication, and blood collection

[0161] 3.1 Grouping and sample processing

[0162] ① Sample preparation: prepare a sufficient amount of sodium heparin anticoagulant centrifuge tubes one day before the animal experiment. Prepare the ellagic acid suspension (control substance) and EANS suspension (test substance) for intragastric administration and use them immediately. Vortex mix before administration.

[0163] ② Heparin sodium centrifuge tube: prepare 1 mg / mL heparin sodium solution, fill a 1.5 mL centrifuge tube with the heparin sodium solution and then pour it out to fully moisten the centrifuge tube, and dry it in a 50°C oven.

[0164] ③ Preparation of ellagic acid free group (control substance): weigh 300 mg of ellagic acid standard into a 50 mL centrifuge tube, add 30 mL of ultrapure water to prepare 10 mg / mL ellagic acid suspension, add 0.15 g of CMC-Na and vortex to mix, and filter the suspension through a syringe needle to obtain the intragastric solution.

[0165] ④ Preparation of EA NS lyophilized powder group (test sample): 375 mg of EANS lyophilized powder was weighed into a 50 mL centrifuge tube, 30 mL of ultrapure water was added to prepare a suspension with an ellagic acid content of 10 mg / mL, 0.15 g of CMC-Na was added and vortexed, and the suspension was filtered through a syringe needle to obtain an intragastric solution. Because previous studies have shown that the ellagic acid content in the lyophilized powder of ellagic acid nanosuspension is 80% (see Example 10 for details), this configuration makes the dosage of ellagic acid in groups ③ and ④ the same.

[0166] 3.2 Medication and Blood Collection

[0167] Rats were fasted overnight one day in advance and given drugs by gavage at a dose of 100 mg / kg. The timing was immediately after gavage. Blood was collected from the control group and the test group at 10min, 20min, 30min, 1, 1.5, 2, 2.5, 3, 4, 6, 8, 10, and 12h. 0.2-0.3mL was collected from the orbits of the control group and the test group. The blood was collected in a sodium heparin centrifuge tube. The sodium heparin centrifuge tube was rotated while the blood was collected to prevent blood coagulation, and cotton balls were used to stop bleeding. After marking the centrifuge tube, vortexed for 5s, centrifuged at 4000r / min at 4℃ for 5min in a refrigerated centrifuge, and stored in a -20℃ refrigerator after plasma separation. The drug-containing plasma was treated according to the method in "Example 12 1", and the volume was 150μL after methanol reconstitution. The HPLC injection analysis was performed according to the method in "Example 12 2". Two other rats were anesthetized by intraperitoneal injection of sodium pentobarbital (dose: 60 mg / kg), and blood was collected from the abdominal aorta into anticoagulated blood collection tubes. The plasma was separated according to the above method and used as blank plasma.

[0168] 3.3 Calculation and statistical analysis of pharmacokinetic parameters

[0169] The plasma drug concentration at each time point was calculated, and the non-compartmental model fitting of the drug-time curve in rats was performed using Phoenix WinNonlin 8.1 software to calculate the pharmacokinetic parameters, and the pharmacokinetic parameters between the groups were compared using SPSS 18.0 software. Fig.11 , it can be seen that both groups generally have a double peak phenomenon; WinNonlin software was used to calculate the pharmacokinetic parameters and are listed in Table 13. It can be seen that the two peak times of blood drug concentration in the EA group were 0.292±0.118 and 2.400±0.224h after taking the medicine, respectively, and the EANS group had a significant delay of 0.833±0.408 (P<0.5) and 3.000±0.548h (P<0.1). In terms of peak concentration, the EANS group showed an increase, among which the increase in the first peak concentration was the most significant, from 0.184±0.064μg·mL -1 Increased to 1.091±0.959μg·mL -1 (P<0.5), the second peak concentration increased from 0.233±0.095μg·mL -1 Increased to 0.368±0.263μg·mL -1 The nanosuspension process increases the in vivo AUC of ellagic acid 0-∞ From 0.329±0.119μg·h·mL -1 Increased to 1.543±0.892μg·h·mL -1(P<0.1), and the relative bioavailability was evaluated by dividing it, which was 4.69 times. The above results show that the ellagic acid nanosuspension greatly promotes the in vivo absorption of ellagic acid raw materials through a significant increase in solubility and multiple in vivo absorption of the drug, but does not significantly prolong the in vivo circulation time of the drug.

[0170] Table 13 Main pharmacokinetic parameters (n=8)

[0171]

[0172] Note: Compared with EA, *P<0.5, **P<0.1, ***P<0.01

[0173] Example 13 Evaluation of Antioxidant Properties of Ellagic Acid Nanosuspension Lyophilized Powder

[0174] 1.DPPH free radical scavenging rate experiment

[0175] The experimental method refers to 2. DPPH free radical scavenging rate test in Example 5.

[0176] Results from Fig.12 -A shows that within the range of ellagic acid mass concentration of 1.28–50 μg / mL, as the mass concentration increases, the scavenging rates of EA, EA NS freeze-dried powder and positive control VC for DPPH free radicals also increase. When a certain mass concentration is reached, the scavenging rate gradually tends to be stable. At each concentration, the scavenging ability of EA NS for DPPH free radicals is significantly higher than that of ellagic acid, with statistical differences (P<0.05). This trend increases with the increase of the administration concentration. The scavenging ability of EA NS for DPPH free radicals is even stronger than that of the positive control VC (P<0.05).

[0177] 2. Total reducing power test

[0178] The experimental method refers to 3. Total reducing power determination test in Example 5.

[0179] Fig.12 -B results were similar to the DPPH clearance results. At each concentration range of ellagic acid mass concentration of 1.28–50 μg / mL, the reducing ability of EA NS to potassium ferrocyanide was significantly higher than that of EA, with statistical significance (P<0.05). Their total reducing power was stronger than that of the positive control VC (P<0.05).

[0180] The above results comprehensively illustrate that after ellagic acid was prepared into nanosuspension by ultrasonic method, its antioxidant property was significantly enhanced.

[0181] Example 14 Structural Characterization of EA BS Lyophilized Powder

[0182] 1.UHPLC-MS / MS

[0183] Take 2.4 mg of sample and dissolve it in 10 mL of mass spectrometry grade methanol, then take 21 μL of it and dissolve it in 10 mL of mass spectrometry grade methanol to prepare the test solution. 1.6 Software-controlled quadrupole mass spectrometer Triple-Quad 5500 (ABSCIEX, USA) analysis. Mass spectrometry detection was performed in negative mode using an electrospray ionization (ESI) source. The ion spray voltage and detection temperature were -4500 V and 550 ° C, respectively. Curtain gas (CUR), ion source gas 1, and ion source gas 2 were set to 35, 55, and 55 psi, respectively. The entrance potential (EP) and collision exit potential (CXP) were set to -10.0 V and -17.0 V, respectively.

[0184] 2. Fourier Transform Infrared Spectrometer (FTIR)

[0185] Fourier transform infrared spectroscopy at 4000-400 cm -1 The range is recorded in transmittance with a resolution of 1cm -1 , samples compressed with KBr, were analyzed using a Bruker IFS 66v / S spectrometer (Bruker, Billerica, MA, USA).

[0186] 3. X-ray powder diffraction (XRPD)

[0187] XRPD was performed on a Johansson monochromator (λCu ) were performed on a SmartLab9kW (Rigaku, Japan) equipped with a LynxEye strip detector with a 2θ angle range of 5–60° and a scan rate of 2° / min.

[0188] 4. Thermal stability

[0189] The sample (3 mg) was placed in an aluminum pan. After sealing, the temperature was raised from 25°C to 600°C at a heating rate of 10°C / min. The thermal stability was measured by using thermogravimetric analysis (TG)-differential scanning calorimetry (DSC) (TA Q200 and TA DSC25, New Castle, USA).

[0190] The above experiments all tested three samples: EA, EA NS, and EA hydrate. The experimental results are summarized as follows: UHPLC-MS / MS results ( Fig.13) shows the secondary mass spectra of EA, EA NS and EA hydrate at a collision voltage of 38 eV in negative ion mode. According to the molecular structure and mass-to-charge ratio, there are many fragment ions with high response in EA, while only two ion fragments are observed in EA NS, m / z=301.1 and m / z=255.2, which are surprisingly similar to the ion fragments of EA hydrate. In summary, the molecular weight of EA NS freeze-dried powder itself has not changed, and it is speculated that it is structurally similar to ellagic acid hydrate.

[0191] Fourier transform infrared spectroscopy FTIR ( Fig.14 -C) The results showed that the raw material EA had hydroxyl absorption peaks at 3556cm-1 and 3475cm-1, while the hydroxyl absorption peak at 3475cm-1 of EA NS disappeared. This may be because the ortho-phenolic hydroxyl groups of the EA molecules are easy to form intramolecular hydrogen bonds, and the participation of water in the ultrasonic preparation process allows these hydrogen bonds to be opened and participate in the formation of new structures, which shows that the ultrasonic preparation process has an impact on the molecular structure; combined with the above UHPLC-MS / MS results and the molar composition of EA NS is EA: water ≈ 1:4 (Example 10), it is speculated that EA NS is also a hydrate of EA, and water molecules participate in the self-assembly process.

[0192] From the DSC results, we can see that Fig.14 -A), the melting point of the raw material EA is 476.5℃, while the melting point of EA NS moves to the right, and the endothermic peak is wider than that of EA and shows a "bulging" type, indicating that unlike EA, when EA NS melts itself, some other components participate in the collapse of its crystal structure.

[0193] The TG graphs of EA NS and EA show great differences ( Fig.14 -B), corresponding to the DSC graph, EA maintained a stable mass after dehydration at 100°C, and suddenly lost weight at 434.23°C; EA hydrate lost more weight than EA at 100°C due to the presence of water, and the subsequent process showed a curve similar to that of EA; while EA NS showed continuous weight loss, and the desolvation process was slow, and the initial desolvation temperature (88.69°C) was lower than the boiling point of the solvent, indicating that the crystal form of EA NS had changed. From XRPD ( Fig.14 -D) found that the raw material EA has a strong diffraction peak, indicating that it exists in the form of crystals; while the diffraction peaks at 12.19°, 17.38°, 25.01°, 28.18°, and 31.64° in EA NS are basically retained, and some diffraction peaks such as 20.51° and 23.80° have undergone varying degrees of changes, further indicating that the crystalline form of EA NS has changed. Based on the above results, it is speculated that EA NS may be a tunnel-type hydrate, "water" exists in the tunnel of the unit cell, and its crystal form has changed compared to the raw material EA.

[0194] It should be noted that the TG-DSC and XRPD of EA hydrate (CAS No.: 314041-08-2, ellagic acid monohydrate) showed different results from EA NS and were more similar to EA. The molar composition of EA NS was EA:water≈1:4 (Example 10), while EA hydrate was a monohydrate, indicating that EA NS and EA hydrate were not the same substance.

Claims

1. A method for preparing an ellagic acid nanosuspension with high solubility and antioxidant activity, characterized in that: The ellagic acid powder is added to a preparation solvent and prepared by an ultrasonic process; the ultrasonic process conditions are: ellagic acid feed concentration ≥2.5 mg / mL, ultrasonic power ≥100 w, ultrasonic frequency ≥20 kHz, ultrasonic temperature ≥30°C, and ultrasonic time ≥5 min; the preparation solvent is pure water or a mixed solution of an organic solvent and water, the organic solvent is selected from one or more of ethanol, propylene glycol, butylene glycol, and pentanediol, and the ratio of the organic solvent to water in the mixed solution of the organic solvent and water is 0:1-3:

1.

2. The method for preparing the ellagic acid nanosuspension according to claim 1, characterized in that: The preparation solvent is water.

3. The method for preparing the ellagic acid nanosuspension according to claim 1, characterized in that: The ellagic acid feed concentration is ≥20 mg / mL.

4. The method for preparing the ellagic acid nanosuspension as claimed in any one of claims 1 to 3, characterized in that: The ellagic acid feed concentration is 20 mg / mL.

5. The method for preparing the ellagic acid nanosuspension according to any one of claims 1 to 3, characterized in that: The ultrasonic temperature is ≥35°C.

6. The method for preparing the ellagic acid nanosuspension according to claim 5, characterized in that: The ultrasonic temperature is 45°C.

7. The ellagic acid nanosuspension prepared by the preparation method according to any one of claims 1 to 6.

8. The ellagic acid nanosuspension according to claim 7, characterized in that: Contains ellagic acid nanoparticles with a diameter of 100-1000 nm.

9. The ellagic acid nanosuspension according to claim 7 or 8, characterized in that: The solid obtained after drying the ellagic acid nanosuspension has a molar ratio of ellagic acid: water = 1:

4.

10. Use of the ellagic acid nanosuspension according to any one of claims 7 to 9 in the preparation of an external preparation or an oral preparation.

11. The use according to claim 10, characterized in that: The external preparation is a cosmetic.